1998
DOI: 10.1097/00005373-199810000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Contusion of Skeletal Muscle Increases Leukocyte-Endothelial Cell Interactions

Abstract: In the mid-term to long-term stages of skeletal muscle injury associated with contusion, a significant portion of tissue damage is secondary to leukocyte-endothelial cell interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
4
9
0
1
Order By: Relevance
“…We concluded that a 3-cm defect is not a consistent nonunion model and that cmpty defects longer than 3 cm without treatment would probably result in a 100% nonunion rate. This is corroborated by the finding of Hertel et al that a 7-cm defect did not show a spontaneous healing response (4).…”
Section: Replysupporting
confidence: 63%
See 3 more Smart Citations
“…We concluded that a 3-cm defect is not a consistent nonunion model and that cmpty defects longer than 3 cm without treatment would probably result in a 100% nonunion rate. This is corroborated by the finding of Hertel et al that a 7-cm defect did not show a spontaneous healing response (4).…”
Section: Replysupporting
confidence: 63%
“…The animal model described by Hertel et al (4) consists of a segmental tibial defect in sheep, stabilized with a custom-made A 0 unreamed interlocking tibial nail. Their model is similar to ours except that we used thrcc instead of two interlocking bolts proximal and distal to the defect.…”
Section: Replymentioning
confidence: 99%
See 2 more Smart Citations
“…Trauma-induced structural and functional damage to the local host tissue causes devascularization, malperfusion, disturbance of endothelial permeability, hypoxia, acidosis, hematoma, edema and increased intracompartmental pressure [10,11,17,39]. In vivo microscopy studies by Menth-Chiari et al (1998) and Schaser et al (1999) demonstrated that the damaging effects of closed soft tissue trauma result in a substantial and sustained impairment of nutritive perfusion, indicated by a significant reduction in functional capillary density [24,32]. This may result in an impaired humoral and cellular immune competence [15].…”
Section: Introductionmentioning
confidence: 99%